2007
DOI: 10.1074/jbc.m609915200
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for the Dynein Light Chain km23-1 in a Smad2-dependent Transforming Growth Factor-β Signaling Pathway

Abstract: We have identified km23-1 as a novel transforming growth factor-␤ (TGF␤) receptor (T␤R)-interacting protein that is also a light chain of the motor protein dynein (dynein light chain). Herein, we demonstrate by sucrose gradient analyses that, in the presence of TGF␤ but not in the absence, km23-1 was present in early endosomes with the T␤Rs. Further, confocal microscopy studies indicate that endogenous km23-1 was co-localized with endogenous Smad2 at early times after TGF␤ treatment, prior to Smad2 translocati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
75
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(83 citation statements)
references
References 88 publications
4
75
4
Order By: Relevance
“…Additional studies demonstrated that kinasenegative T␤Rs are required for km23-1 effects (23,27). km23-1 was also required for both Smad2-dependent and Smad-independent TGF␤ responses (23,27,32). In the current report, we describe a novel role for km23-1 in linking Ras activation by TGF␤ to TGF␤ autoinduction in TGF␤-sensitive epithelial cells.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…Additional studies demonstrated that kinasenegative T␤Rs are required for km23-1 effects (23,27). km23-1 was also required for both Smad2-dependent and Smad-independent TGF␤ responses (23,27,32). In the current report, we describe a novel role for km23-1 in linking Ras activation by TGF␤ to TGF␤ autoinduction in TGF␤-sensitive epithelial cells.…”
mentioning
confidence: 55%
“…km23-1 interacts with and co-localizes in early endosomes with T␤RII and Smad2 after TGF␤ treatment (23,32). Moreover, km23-1 undergoes rapid phosphorylation on serine residues after T␤R activation, in keeping with the kinase specificity of the T␤Rs (23).…”
mentioning
confidence: 86%
“…The motor protein dynein light chain km23-1 has been shown to bind TbRII and to be phosphorylated after TGF-b stimulation (Tang et al 2002). km23-1 promotes both Smad-dependent (Jin et al 2007a) and Smad-independent signaling. In contrast, the motor protein dynein light chain Tctex2b associates with the short cytoplasmic tail of endoglin in endothelial cells and with TbRII and betaglycan in endothelial and other cell types, providing negative regulation of TGF-b signaling (Meng et al 2006).…”
Section: Cytoplasmic Kinases: Cgkimentioning
confidence: 99%
“…Smads are sequestered away from the receptors when bound to microtubules, from where they can be released, for example, by connexin 43 (GJ1), which competes with microtubules to bind Smads . Additional motor proteins, such as the dynein light chain km23-1 (DYNLRB1), also promote Smad traffic towards the nucleus of mammalian cells (Jin et al, 2007). The developmental roles of the connexin 43 and km23-1 mechanisms have not yet been specifically addressed.…”
Section: Regulation Of Smad Trafficking By Motor Proteinsmentioning
confidence: 99%